INTEGRATION OF SHALAWAT IN ISLAMIC BOARDING SCHOOL EDUCATION MANAGEMENT (BUILDING RELIGIOUS CULTURE AND SPIRITUAL LEADERSHIP) - Ahmad Walid; Tutik Hamidah; Amar Ma'rup Nahi Munkar (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The phenomenon of the integration of prayer in the management of Islamic boarding school education is an important topic to study in the context of the development of religious culture and spiritual leadership in Islamic educational institutions. This study aims to explore how the integration of prayer can build religious culture and spiritual leadership in Islamic boarding schools. A qualitative approach with a case study method is used to explore this phenomenon. Data were collected through in-depth interviews, participatory observations, and documentation in several Islamic boarding schools in Madura, East Java. The results of the study show that shalawat plays a significant role in the daily life of students and the management of Islamic boarding schools. The integration of prayer helps create a religious atmosphere, improve student discipline, and strengthen spiritual leadership in Islamic boarding schools. The implication of this study is the importance of adopting the integration of prayer as a managerial strategy in pesantren education to form religious character and effective leadership.